2004
DOI: 10.1161/01.cir.0000143144.82338.36
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prehospital Thrombolysis for Acute Myocardial Infarction on 1-Year Outcome

Abstract: for the USIC 2000 InvestigatorsBackground-Limited data are available on the impact of prehospital thrombolysis (PHT) in the "real-world" setting. Methods and Results-Of 443 intensive care units in France, 369 (83%) prospectively collected all cases of infarction (Յ48 hours of symptom onset) in November 2000; 1922 patients (median age, 67 years; 73% men) with ST-segment-elevation infarction were included, of whom 180 (9%) received intravenous thrombolysis before hospital admission (PHT). Patients with PHT were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
35
0
11

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(53 citation statements)
references
References 21 publications
7
35
0
11
Order By: Relevance
“…The mean age of patients enrolled ranged from 57 to 80 years in the RCTs and from 57 to 91 years in the observational studies. Two RCTs 2,4 and 7 observational studies 23,35,39,49,61,62 reported prehospital administration of fibrinolytic therapy. Fibrin-specific agents were used primarily in 16 RCTs 1-4,6 -12,14,15,19,20,22 and 11 observational studies 24,33,35,37,41,43,44,48,53,57,61 (Tables I and II of Primary PCI was associated with an Ϸ34% short-term reduction in mortality (OR, 0.66; 95% CrI, 0.51 to 0.82) in RCTs ( Figure 2) and an Ϸ23% lower mortality in observational studies (OR, 0.77; 95% CrI, 0.62 to 0.95; Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age of patients enrolled ranged from 57 to 80 years in the RCTs and from 57 to 91 years in the observational studies. Two RCTs 2,4 and 7 observational studies 23,35,39,49,61,62 reported prehospital administration of fibrinolytic therapy. Fibrin-specific agents were used primarily in 16 RCTs 1-4,6 -12,14,15,19,20,22 and 11 observational studies 24,33,35,37,41,43,44,48,53,57,61 (Tables I and II of Primary PCI was associated with an Ϸ34% short-term reduction in mortality (OR, 0.66; 95% CrI, 0.51 to 0.82) in RCTs ( Figure 2) and an Ϸ23% lower mortality in observational studies (OR, 0.77; 95% CrI, 0.62 to 0.95; Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…There was no conclusive difference in mortality in the meta-analysis of observational studies that used prehospital fibrinolytic therapy. 23,35,39,49,61,62 An estimate of the difference in mortality between primary PCI and prehospital fibrinolytic therapy could not be done with certainty because only 2 RCTs used prehospital fibrinolysis. 2,4 In RCTs, primary PCI was associated with a 24% reduction in long-term mortality (OR, 0.76; 95% CrI, 0.58 to 0.95; Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…В рандомизированном исследовании CAPTIM, посвященном сравнению первичного ЧКВ и догоспи-тального тромболизиса (c проведением при необходимо-сти спасительной ЧКВ) [28,29] показана сходная частота неблагоприятных исходов. Регистровые исследования подтверждали эти данные [30]. Более того у больных, получивших тромболитик в пределах двух часов от начала ОИМ, отмечена тенденция к меньшей, чем при исполь-зовании ЧКВ, смертности [29,31].…”
Section: сокращение задержки с реперфузией -ключ к спасе-нию погибающunclassified
“…Для того чтобы максимально «приблизить» реперфузионную терапию к пациенту, а значит, умень-шить время до реперфузии и спасти максимально больший объем миокарда, необходимо провести ТЛТ на догоспитальном этапе. В одном из первых исследо-ваний, посвященном изучению эффективности до-госпитального тромболизиса, было показано, что при проведении его больным ИМпST госпиталь-ная смертность составила 3,3 %, тогда как при прове-дении ТЛТ в стационаре -8 %, а при отсутствии ре-перфузионной терапии -12,2 %, однолетняя выживаемость больных составила 94, 89 и 79 % соот-ветственно [14].…”
unclassified